Introducing and Expanding Newborn Screening in the MENA Region - Victor Skrinska; Issam Khneisser; Peter Schielen; Gerard Loeber (International Journal of Neonatal Screening, 2020)
This special edition of the International Journal of Neonatal Screening includes the presentations of the fourth Meeting of the Middle East North Africa (MENA) Region of the International Society for Neonatal Screening (ISNS) held in Limassol, Cyprus, March 8−11, 2020 [...]